2005
DOI: 10.1128/mcb.25.20.9073-9081.2005
|View full text |Cite
|
Sign up to set email alerts
|

GCF2/LRRFIP1 Represses Tumor Necrosis Factor Alpha Expression

Abstract: Tumor necrosis factor alpha (TNF-␣) is an important mediator of inflammation, apoptosis, and the development of secondary lymphoid structures. Multiple polymorphic microsatellites have been identified in and around the gene, and there are also multiple single-base pair biallelic polymorphisms in the introns and promoter. The TNF-␣ ؊308 promoter polymorphism is a G-to-A transition which has been statistically associated with various autoimmune disorders. Some studies have found that it may directly mediate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 58 publications
(50 reference statements)
0
60
0
1
Order By: Relevance
“…LRRFIP2 interacts with Dvl to increase the cellular levels of ␤-catenin for activating ␤-catenin/LEF (lymphocyte enhancer binding factor)/TCF (T cell factor)-dependent transcriptional activity (16). Flap-1 or LRRFIP1 was also shown to bind the TNF-␣-308 promoter polymorphism site, suggesting its possible role in the regulation of TNF-␣ production (17). However, the functional role of LRRFIP2 and Flap-1 in innate immune responses is largely unexplored, although we previously observed by using a luciferase reporter assay that the LRRFIP2 homolog, Flap-1, modestly activates NF-B (10).…”
mentioning
confidence: 99%
“…LRRFIP2 interacts with Dvl to increase the cellular levels of ␤-catenin for activating ␤-catenin/LEF (lymphocyte enhancer binding factor)/TCF (T cell factor)-dependent transcriptional activity (16). Flap-1 or LRRFIP1 was also shown to bind the TNF-␣-308 promoter polymorphism site, suggesting its possible role in the regulation of TNF-␣ production (17). However, the functional role of LRRFIP2 and Flap-1 in innate immune responses is largely unexplored, although we previously observed by using a luciferase reporter assay that the LRRFIP2 homolog, Flap-1, modestly activates NF-B (10).…”
mentioning
confidence: 99%
“…MMP15 is a member of the matrix metalloproteinase (MMP) family and promotes ECM remodeling (36). LRRFIP1 (leucinerich repeat (in FLII)-interacting protein 1), which is an ECM component, occupies a tumor necrosis factor-␣ (TNF-␣) promoter site and appears to act as a repressor of TNF-␣ production (37). PLXND1 (Plexin D1) (38) and ANGPTL1 (angiopoietin-like 1) (39) are both associated with vasculogenesis and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution of G with A at nucleotide positions −308 and −238 in the TNF-α promoter region enhances transcription of this cytokine in cultured cells [18,19], although other studies suggest otherwise [20]. However has also been previously suggested that increased expression of TNF-α in adipocytes may influence insulin sensitivity [5].…”
Section: Discussionmentioning
confidence: 99%